Fault Tolerant Dynamic Scheduling on Real Time Hierarchical System: Proposals for Fault Tolerant Mechanism on Safety-Critical System - Wirawan Wijiutomo, Catur; Riyanto Trilaksono, Bambang; Imam Kistijantoro, Achmad (International Journal of Engineering and Technology, 2018)
The paradigm changes from federated architecture to integrated architecture in the real time system introduces a partitioned system to ensure fault isolation and for scheduling the hierarchy scheduling at the global level between partition and local in partition. Integrated architecture based on partitioned system with hierarchical scheduling is referred as real time hierarchical system which is a solution to increase efï¬ciency in terms of hardware cost and size. This approach increasing the complexity of the integration process including the handling of faults. In this paper the authors describe a proposal with three components for dealing with fault tolerant in real time hierarchical systems by handling fault in task level, partition level and distributed level. The contribution of this proposal is the mechanism for building fault tolerant system on real time hierarchical system.Â Â  Â